Modifying the methods of treatment of mothers of the mentally handicapped - a field study in the psychological center - SI BACHIR, Karima; SACI, Karima (Social Sciences Journal)
The study aimed to amend the mothers’s abnormal treatment of their children who develop mental retardation, through the proposed- counseling program. It also aimed to provide them with information, educational experience and concepts about the nature of this mental retardation. Moreover, it highlights the characteristics of these children aiming at encouraging these women to accept their children and their illness by providing them with special skills of training. The researcher adopted the method of the collective guidance because it provides the exchange of experience, the unity of purpose and opportunities to express their reaction in an acceptable manner. It also achieves good results with regard to learning, leading to agreement on common solutions by the group, fosters confidence and mutual cooperation between the participants. The sample study was made up of 15 mentally-retarded children’s mothers. The women were randomly chosen while the program was applied for 8 weeks. Besides, the duration of each session was (60) minutes. After the implementation of the program, the researcher adopted the dimensional approach to identify the continuity‘s extent of the program. The research relied on the Dependent Sample T-Test in order to examine the significant differences of the average level with regard to the parental treatment’s methods. Hence, it resulted in the following .There are statistically significant differences at the average level of the methods of parental treatment between pre and مجلة العلوم االجتماعية العدد 22 جانفي 2017 137 pro evaluations due to the application of the counseling program. Thus, applying the program can amend the mothers’s treatment methods to their children. There are statistically significant differences at the average level of the methods of parental methods between pre and follow- up evaluations due to the application of the counseling program to the mothers of mentally-retarted children